(untitled) (Patan Prospective Journal, 2025)
Inflation remains a key macroeconomic concern in Nepal, with important implications for economic stability, purchasing power, and policy effectiveness. Despite its relevance, empirical studies using recent data and modern time-series methods are limited. This study examines the determinants of inflation in Nepal using annual data from 1993 to 2024 and applies the Autoregressive Distributed Lag (ARDL) and Error Correction Model (ECM) framework. The ARDL approach is suitable for this analysis as it accommodates variables integrated of different orders and performs well in small samples. The model incorporates both domestic and external determinants of inflation, including GDP growth, broad money growth, remittances as a share of GDP, and Indian inflation. Unit root tests confirm mixed integration orders, and the ARDL bounds test provides strong evidence of a long-run cointegrating relationship among the variables. The empirical results indicate that inflation in Nepal is primarily driven by external price transmission and remittance-induced demand pressures. In the long run, Indian inflation and remittances have a positive and statistically significant effect on domestic inflation, reflecting Nepal’s strong trade dependence on India and the demand-side impact of large remittance inflows. In contrast, GDP growth and broad money growth do not show significant long-run effects, suggesting weak domestic demand pressure and limited monetary transmission. Short-run dynamics reveal rapid adjustment toward long-run equilibrium, as indicated by a significant error correction term. Diagnostic and stability tests confirm the robustness of the model. Overall, the findings suggest that effective inflation control in Nepal requires coordinated policies that address external price shocks, improve domestic supply capacity, and promote the productive use of remittances alongside conventional monetary policy.